The Power of Psychoeducation: An Effort to Increase Understanding of ADHD Among Parents and Teachers - Wardani, Fadila Dian; Dewi, Damajanti Kusuma (Proceedings of The International Conference on Psychology and Education, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is one of the neurodevelopmental disorders that often occurs in children with a prevalence of 7.2% in children under 18 years of age according to a meta-analysis of 175 global studies in 2015. This high prevalence has not been balanced with the understanding of parents and teachers due to the lack of information, resulting in inappropriate treatment of children with ADHD. Psychoeducation plays an important role in providing accurate information about the symptoms, causes, and treatment of ADHD. We tried to explore the influence of psychoeducation on parents' and teachers' understanding of ADHD. This study used a systematic review method by collecting data from PubMed, ScienceDirect, and Google Scholar. The selected articles were articles published in the last 5 years with a focus on ADHD psychoeducation in children with a population of parents and teachers. Data analysis used the PRISMA model which produced 35 research articles that passed the systematic review. The results showed that psychoeducation can improve understanding, change misunderstandings, improve skills, and provide support for parents and teachers in dealing with children with ADHD. This study emphasizes the importance of structured psychoeducation for parents and teachers in efforts to disseminate information about ADHD.